2020
DOI: 10.2147/dmso.s256223
|View full text |Cite
|
Sign up to set email alerts
|

<p>Synergistic Association of Carcinoembryonic Antigen and Carbohydrate Antigen 19-9 on the Risk of Abnormal Glucose Regulation</p>

Abstract: Purpose: Carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA19-9) are tumor-associated antigens. An increased serum level of CEA and CA19-9 separately has been reported in diabetes. In this study, we examined the composite effect of elevated serum levels of both CEA and CA19-9 on subjects with type 2 diabetes and prediabetes. Patients and Methods: A total of 3568 adults who attended a health examination were enrolled into this cross-sectional study. Subjects were grouped into four groups according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 64 publications
(70 reference statements)
1
7
0
Order By: Relevance
“…Multiple studies have found that the elevation of CEA occurred more frequently in patients with diabetes than in patients without diabetes, and the elevated CEA in diabetic patients was associated with HbA1c and reversible. 6,7,23 These results were consistent with our study results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Multiple studies have found that the elevation of CEA occurred more frequently in patients with diabetes than in patients without diabetes, and the elevated CEA in diabetic patients was associated with HbA1c and reversible. 6,7,23 These results were consistent with our study results.…”
Section: Discussionsupporting
confidence: 93%
“…5 Studies showed that diabetic patients had significantly higher rates of abnormal tumor markers than those without diabetes, including carcinoembryonic antigen (CEA), carbohydrate antigens, neuron-specific enolase (NSE), and cytokeratin 19 fragment (CYFRA 21-1). [6][7][8] The relationship between diabetes and cancer is uncertain. However, tumor markers in diabetic patients are significantly elevated.…”
Section: Introductionmentioning
confidence: 99%
“…6 However, it was showed that diabetic patients had significantly higher rates of elevated CEA than subjects without diabetes. [7][8][9] We found that there was a short-term elevation of CEA in diabetic inpatients, and there was a significant difference in HbA1c between the elevated CEA group and the group with normal CEA. 10 However, due to the insufficient number of patients, correlation analysis was not conducted in our last study.…”
Section: Introductionmentioning
confidence: 67%
“…In a follow-up study, increased serum CEA may also account for the progression of coronavirus disease 2019 [ 27 ], more frequent fracture incidence [ 28 ], severity of heart failure (HF), HF adverse prognosis [ 29 ], CVD events and all-cause mortality [ 10 ]. Furthermore, elevated serum CEA may be an important risk factor for prediabetes and T2D [ 11 ], and the levels of serum CEA are closely associated with poor glycaemic control [ 30 ] and oxygen desaturation index [ 31 ] in patients with T2D. Regarding diabetic complications, higher serum CEA levels may independently contribute to macroalbuminuria in patients with diabetes [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased serum CEA levels are not only cross-sectionally associated with obesity, metabolic syndrome, and leukoaraiosis of the brain [7][8][9] but can also longitudinally predict cardiovascular events and mortality in the general population [10]. Additionally, serum CEA levels are increased in patients with prediabetes and type 2 diabetes (T2D) and are associated with diabetic complications, such as diabetic nephropathy [11,12]. Nevertheless, the relationship between serum CEA levels and DPN in T2D has not been well investigated.…”
mentioning
confidence: 99%